Education About Trunk stability training For Balance In Elementary School Students (JURNAL PENGMAS KESTRA (JPK), 2025)
Balance is a fundamental component of motor development in elementary school students, as it plays a crucial role in supporting functional activities, learning processes, and children’s participation in daily physical activities. During elementary school age, balance ability is still developing and therefore requires appropriate, structured, and age-specific movement stimulation. One effective approach to improving balance is trunk stability training, which focuses on strengthening and controlling the core muscles. Core muscles are essential for maintaining postural stability, enhancing body control, and supporting efficient movement of the extremities. This community service program aimed to provide education and practical training on trunk stability exercises as a promotive and preventive strategy to improve balance in elementary school students. The implementation method consisted of three stages: preparation, implementation, and evaluation. The implementation stage included theoretical education and practical trunk stability exercises tailored to the students’ age and physical abilities. Evaluation was conducted through observation and simple assessments of students’ balance abilities and levels of understanding before and after the program. The results demonstrated a significant improvement in students’ understanding of the importance of trunk stability, with the proportion of students categorized as having good understanding increasing from 30% to 70%, while those in the moderate category decreased from 50% to 25%, and the poor understanding category declined from 20% to 5% after the intervention. Additionally, improvements were observed in both static and dynamic balance performance, as indicated by increased single-leg standing duration and better postural control during movement activities. Teachers provided positive feedback, highlighting the program’s practicality and relevance to school-based physical activities. In conclusion, trunk stability training education is an effective, applicable, and sustainable approach to supporting health promotion and motor development in elementary school students.